Definition and characterization of novel HLA-*A02-restricted CD8 + T cell epitopes derived from JCV polyomavirus with clinical relevance - Mani, Jiju; Wang, Lei; Hückelhoven-Krauss, Angela; Schmitt, Anita; Jin, Nan; Kleist, Christian; Ho, Anthony Dick; Schmitt, Michael (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.12387 Jiju Mani, Lei Wang, Angela G. Hückelhoven, Anita Schmitt, Alma Gedvilaite, Nan Jin, Christian Kleist, Anthony D. Ho, Michael Schmitt
Published 01 October 2016
Gesehen am 14.09.2018